2137. Effectiveness of Four Vaccines in Preventing SARS-CoV-2 Infection in Kazakhstan. (15th December 2022) - Nabirova, Dilyara; Horth, Roberta; Nukenova, Gaukhar; Smagul, Manar; Yesmagambetova, Aizhan; Singer, Daniel; Henderson, Alden; Tsoy, Alexey
Abstract: Background: In February 2021 Kazakhstan began offering COVID-19 vaccines to adults. Breakthrough SARS-CoV-2 infections raised concerns about real-world vaccine effectiveness. We aimed to evaluate effectiveness of four vaccines against SARS-CoV-2 infection. Methods: We conducted a retrospective cohort analysis among adults in Almaty using aggregated vaccination data and individual-level breakthrough COVID-19 cases (≥14 days from 2 nd dose) using national surveillance data. We ran time-adjusted Cox-proportional-hazards model with sensitivity analysis accounting for varying entry into vaccinated cohort to assess vaccine effectiveness for each vaccine (measured as 1-adjusted hazard ratios) using the unvaccinated population as reference (N=565, 390). We separately calculated daily cumulative hazards for COVID-19 breakthrough among vaccinated persons by age and vaccine month. Results: From February 22 to Sept 1, 2021 in Almaty, 747, 558 (57%) adults were fully vaccinated (received 2 doses) and 108, 324 COVID-19 cases (11, 472 breakthrough) were registered. Vaccine effectiveness against infection was 78% (sensitivity estimates: 74–82%) for QazVac, 77% (72–81%) for Sputnik V, 71% (69–72%) for Hayat-Vax, and 69% (64–72%) for CoronaVac. Among vaccinated persons, the 90-day follow-up cumulative hazard for breakthrough infection was 2.2%. Cumulative hazard was 2.9% among people aged ≥60 years versus 1.9% among persons aged 18–39 years (p< 0.001), and 1.2% for people vaccinated in February–May versus 3.3% in June–August (p< 0.001). Conclusion: Our analysis demonstrates high effectiveness of COVID-19 vaccines against infection in Almaty similar to other observational studies. Higher cumulative hazard of breakthrough among people >60 years of age and during variant surges warrants targeted booster vaccination campaigns. Disclosures: All Authors : No reported disclosures.